2022
DOI: 10.1007/s12144-022-02913-6
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among the general population and healthcare workers during the COVID-19 pandemic: A meta-analysis of well-being and psychological distress prevalence

Abstract: The COVID-19 pandemic has constituted a global health crisis that has threatened the mental health of individuals worldwide. The present paper sought to systematically review and meta-analyze studies reporting the prevalence during the COVID-19 pandemic of well-being and psychological distress as defined by the dual-continua model, which includes (absence of) psychological distress and (presence of) well-being among the general population and healthcare workers. Systematic searches were conducted in various da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 51 publications
3
23
0
1
Order By: Relevance
“…Self-compassion can help university students deal with their mental health disorders while also helping them increase their psychological well-being. This finding is consistent with previous research investigating the relationships of self-compassion and psychological well-being as protective factors in terms of mental health (Blasco-Belled et al, 2022 ; Neff & McGehee, 2010 ) with psychological distress (Fong & Loi, 2016 ; Hatun & Kurtça, 2022 ; Jiménez et al, 2020 ) or symptoms (Blasco-Belled et al, 2022 ), and also with sleep quality, emotional distress, and mental well-being (Rakhimov et al, 2022 ). In the existing literature, it is noted that there is, regardless of age, a positive association between self-compassion and psychology well-being (Fong & Loi, 2016 ; Hatun & Kurtça, 2022 ; Neff & McGehee, 2010 ) between self-compassion and sleep quality, which in turn helps reduce anxiety and depression (Rakhimov et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Self-compassion can help university students deal with their mental health disorders while also helping them increase their psychological well-being. This finding is consistent with previous research investigating the relationships of self-compassion and psychological well-being as protective factors in terms of mental health (Blasco-Belled et al, 2022 ; Neff & McGehee, 2010 ) with psychological distress (Fong & Loi, 2016 ; Hatun & Kurtça, 2022 ; Jiménez et al, 2020 ) or symptoms (Blasco-Belled et al, 2022 ), and also with sleep quality, emotional distress, and mental well-being (Rakhimov et al, 2022 ). In the existing literature, it is noted that there is, regardless of age, a positive association between self-compassion and psychology well-being (Fong & Loi, 2016 ; Hatun & Kurtça, 2022 ; Neff & McGehee, 2010 ) between self-compassion and sleep quality, which in turn helps reduce anxiety and depression (Rakhimov et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the existing literature, it is noted that there is, regardless of age, a positive association between self-compassion and psychology well-being (Fong & Loi, 2016 ; Hatun & Kurtça, 2022 ; Neff & McGehee, 2010 ) between self-compassion and sleep quality, which in turn helps reduce anxiety and depression (Rakhimov et al, 2022 ). The extant literature also indicates a negative relationship between self-compassion and distress (Fong & Loi, 2016 ) and between psychological well-being and psychological symptoms (Blasco-Belled et al, 2022 ). Therefore, in line with previous studies, this research demonstrates that individuals with high levels of self-compassion experience higher levels of psychological well-being, which in turn decrease mental health disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Over the period of data collection from spring 2020 until the beginning of 2022, both psychological and somatic symptom burden increased significantly in our sample. Publications of data collected early in the pandemic reported deleterious effects on mental health with significantly higher levels of depression and anxiety than pre-pandemic estimates in the general population (Ettman et al, 2020 ; Pierce et al, 2020 ; Nochaiwong et al, 2021 ; Blasco-Belled et al, 2022 ) and in samples of healthcare professionals (Pappa et al, 2020 ; Bekele and Hajure, 2021 ; Hao et al, 2021 ; Blasco-Belled et al, 2022 ). In contrast, some later studies suggest that after an initial peak, psychological distress gradually declined over time until almost returning to baseline levels by mid-2020 (Fancourt et al, 2021 ; Aknin et al, 2022 ; Robinson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The outbreak of the coronavirus disease 2019 (COVID-19) pandemic in early 2020 became not only a global threat to physical health but also negatively affected people's mental wellbeing in different communities (1). Studies reported 2-8 times increased rates of depression, anxiety, insomnia, and stress among the general population since the COVID-19 pandemic (1)(2)(3)(4). Healthcare workers seem even more burdened than the general population (5,6), being not only vulnerable to experiencing physical exhaustion due to the extremely high workloads (7).…”
Section: Introductionmentioning
confidence: 99%